Consumed by Boredom: Food Choice Motivation and Weight Changes during the COVID-19 Pandemic - Wijnand A. P. Van Tilburg; Reinhard Pekrun; Eric R. Igou (Behavioral Sciences, 2022)
Boredom is an established cause and correlate of eating behavior. Yet, existing work offers a scattered range of plausible motivations for why this is. We examined among 302 people representative of the adult UK population what motivations they had for selecting food during the COVID-19 pandemic and how this related to boredom. As predicted, bored people choose food less for health reasons and more for convenience. Boredom reduced ethical and ‘natural content’ motivations for selecting food and was not associated with choosing food to regulate one’s mood or to experience unfamiliarity. Boredom was also associated with greater absolute changes in weight over the course of the pandemic. Boredom did not predict weight gains or losses overall. These findings offer insights into the role that boredom plays in eating motivations in particular and health-relevant outcomes in general.